Akuntabilitas, Transparansi, dan Partisipasi Untuk Good Governance di Kecamatan Teluk Bayur - Satyawati, Salama Qaulam; Fitria, Yunita (Penerbit Goodwood, 2025)
Purpose: This study aims to evaluate the implementation of the principles of accountability, transparency, and participation in the management of the Village Revenue and Expenditure Budget (APBDes) as an effort to realize good governance in Teluk Bayur District, Berau Regency. Methodology: The research method used is a qualitative approach with data collection techniques including interviews, observations, and documentation. Results/findings: The results show that the four villages studied—Tumbit Melayu, Labanan Jaya, Labanan Makmur, and Labanan Makarti—have made efforts to implement these principles in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018, although improvements are still needed in several aspects for optimization. Conclusions: The implementation of accountability, transparency, and participation has shown progress, yet it remains suboptimal. Strengthening community involvement and enhancing administrative capacity are essential to achieving better governance outcomes. Limitations: This study is limited to four villages, uses a qualitative approach that is subjective, and only focuses on three principles of good governance. Future research is suggested to cover a wider area, apply a quantitative approach, and explore other principles such as effectiveness and efficiency. Contribution: The author expresses gratitude to the academic advisor, Ms. Yunita Fitria, to the informants and village officials in Teluk Bayur, and to family and friends for their support during the preparation of this journal.